Language - Mengham, Rod (Fontana Press, 1993)
This study takes a fresh look at language and its resounding significances. It ranges from a survey of the biological knowledge of language, detailing the functions of the brain, a history of writing systems, the linguistic effects of democracy in 5th-century Athens, the spread of the largest family of languages in the world - Indo-European, and the effects on language of writing, printing, telephone and computer networks. The book argues that it is through language that human beings define themselves and the world, and analyzes the way cultures are organized around language, from literary classics to advertising slogans. It uncovers the fundamental role that language plays in the process of social change, and demonstrates how it can be used equally as a force for conservatism or for radical innovation in the formation of nationality and family, gender and class. Using wide-ranging and familiar references, Rod Mengham makes accessible the fruits of the latest cutting-edge research in linguistics, neurology, psychology, superstition, religion, myth and history to a non-specialist audience.